Constructing high‐efficiency microwave shielding networks in multi‐walled carbon nanotube/poly(ε‐caprolactone) composites by adding carbon black and graphene nano‐plates - Sun, Chang; Peng, Wen‐Jie; Huang, Ming‐Lu; Zhao, Kun‐Yan; Wang, Ming (Polymer international, 2023)
Herein, high‐efficiency microwave shielding networks are constructed in multi‐walled carbon nanotube/poly(ε‐caprolactone) (CNT/PCL) composites by adding carbon black (CB) or graphene nano‐plates (GNPs). The synergistic effect of carbonaceous fillers with different rdimensions is investigated to obtain the optimal electromagnetic shielding performance of the composites. The CNT/GNP/PCL, CNT/CB/PCL and CB/GNP/PCL composites with different ratios were prepared by melt mixing and hot press molding for the microwave shielding evaluation. Because of the synergistic effect, the microwave shielding effectiveness values of 53.8 and 54.6 dB, which are achieved in the CNT9/CB1/PCL (CNT:CB = 9:1) and CNT9/GNP1/PCL (CNT:GNP = 9:1) composites, respectively, are higher than the value of 46.4 dB for the CNT/PCL composites with the same filler content of 4.12 vol%. The synergistic effect between carbonaceous fillers is attributed to the high‐efficiency shielding networks which can be easily formed by carbonaceous fillers with different dimensions. © 2023 Society of Industrial Chemistry. The addition of graphene nano‐plates and carbon black particles can form a high‐efficiency conductive network via the ‘bridge’ effect among carbon nanotube particles to enhance electrical conductivity and microwave shielding performance.